PENGARUH SUSTAINABLE ENTREPRENEURIAL ORIENTATION TERHADAP INNOVATION CAPABILITY DAN KINERJA USAHA (Studi pada UMKM di Kabupaten Banyuwangi) (Jurnal Bisnis Indonesia, 2022)
This study aims to determine the factors that influence the business performance of tourism-based SMEs in the Banyuwangi Regency. The magnitude of the failure of MSME actors to maintain business sustainability due to increasingly fierce market competition is the reason to focus on this research. As MSME actors who are still pioneering, it is essential to support entrepreneurship skills and innovation to achieve sustainable business performance. The difficulties entrepreneurs face often stem from lack of knowledge or skills, lack of finance or capital, lack of mastery of information technology, and distribution of services/products produced. The data collected in this study was conducted through a survey of 94 MSME actors working in the tourism sector in the Banyuwangi Regency. Data analysis used Structural Equation Model (SEM) with Partial Least Square (PLS) approach. This study's results show a significant effect of Sustainable Entrepreneurial Orientation on Innovation Capability and Business Performance; Innovation Capability Directly Affects Business Performance on MSMEs in Banyuwangi Regency. This means that the improvement of MSME business performance in Banyuwangi is strongly influenced by the ability of business actors to carry out sustainable development and innovation strategies  DOI : https://doi.org/10.33005/jbi.v13i1.3071